Who would benefit from memory training? A pilot study examining the ceiling effect of concurrent cognitive stimulation - Kwok TCY (Dove Medical Press, 2011)
Timothy CY Kwok1,2, Wai Wang Chau1, Kenneth SL Yuen1,3, Anita YM Wong4, Jessie CY Li1, Rebecca YY Shiu4, Florence KY Ho11Jockey Club Centre for Positive Ageing, Hong Kong; 2Department of Medicine and Therapeutics, The Chinese University of Hong Kong, Hong Kong; 3Laboratory of Neuropsychology, Department of Psychology, University of Hong Kong, Pokfulam, Hong Kong; 4The Hong Kong Chinese Women's Club Madam Wong Chan Sook Ying Memorial Care and Attention Home for the Aged, Hong KongAbstract: Diverse effects of memory training were observed in the literature. One possible factor is the amount of concurrent cognitive training received during the training program. In this pilot study, we recruited 24 elderly adults with or without concurrent cognitive stimulations to attend a memory-training program. Findings suggested that elderly people without concurrent cognitive stimulation could benefit from a memory-training program in the form of improved initiation and memory functioning. Self-rated quality of life measure also showed improvements alongside the cognitive benefits. Elderly people with regular concurrent cognitive stimulation, on the other hand, seemed to plateau in their level of performance and did not show any significant change. Our preliminary findings suggested nonlinear concurrent cognitive stimulation in the elderly.Keywords: memory training, cognitive training, dementia, Chinese, elderly